PENERAPAN MANAJEMEN STRATEGI DALAM PENINGKATAN MUTU MADRASAH - Iskandar, Jamaluddin (Idaarah: Jurnal Manajemen Pendidikan, 2017)
Strategic management is an improvement in the quality of education that has long been applied for the achievement of a predetermined educational goal, which is based on the Act has been determined. Implementation of strategic management includes external internal analysis, and samapai at strategic evaluation stage to find out how far the results have been achieved. In addition, it must be supported by various things including adequate facilities, community support and the surrounding government. Improving the Quality of Education includes the processes and outcomes of education that affect each other. In measuring a certain quality of education if it can be known by looking at various things, among them is the maximum learning process, adequate facilities, professional teachers with various capabilities possessed, to the support of various parties. Based on the results of the discussion, it can be seen that there is a significant influence between the implementation of strategic management with improving the quality of education in all levels of education.